Nanostructured beds for the removal of acid gas - Montenegro Suárez, Andrea Pilar (2023)
The presence of acid gases in natural gas makes the sweetening process a requirement to use it as a source of clean energy, comply with regulations, contribute to the reduction of environmental pollution, and therefore, reduce the damage caused to the health of living beings. One of the most commonly used processes for removing H2S from natural gas is sweetening using solid beds. To take advantage of the ferruginous and titaniferous sands of Ecuador to develop a solid-bed technology capable of competing with those available in the market, spherical and cylindrical pellets of the four composites were prepared at different percentages by weight of CZY-304 clay. SYA-104 sand and ZnO particles. First, the raw material was ground and sieved to < 230 mesh for the clay sample and to < 120 mesh for the SYA-104 sand sample, in addition to magnetically enriching each sand sample. Subsequently, spherical and cylindrical pellets were fabricated using spherical and cylindrical molds, respectively. All the samples were calcined in a muffle furnace at 450 °C for 14 h with a heating ramp of 5 °C/min. Once cylindrical pellets were obtained, porosity and uniaxial compression tests were performed to determine the mechanical properties of the material. The spherical pellets were tested for their reactivity with H2S. Finally, X-ray diffraction characterization and scanning electron microscopy were performed together with elemental analysis of the raw material samples and spherical pellets.